A Time for Change?: Re-Visioning Your Call - Hightower, James; Gilliam, W. Craig (Rowman & Littlefield Publishers, 2000)
Many professional ministers struggle at some point with the desire to pursue another career. For those at such a place on their journey, this book poses questions, offers practical suggestions gathered from other ministers who have traveled this path, and shares insights from the authors' own experiences of career change. The authors emphasize two principles. First, entertaining the possibility of leaving professional ministry is not to be condemned or viewed as a sign of failure; rather, it should be accepted as part of the spiritual journey. Second, a new career apart from the institutional church does not mean one is leaving the ministry, but simply that one is changing the mode of expressing that ministry.